Circular - Braun, Madeleine
011-0081-001 COMITÉ INTERNATIONAL DE COORDINATION ET D'INFORMATION POUR l'AIDE A l'ESPAGNE RÉPUBLICAINE (issu de la Conférence Européenne — Paris - 13 Août 1936) 27, RUE JEAN-DOLENT - PARIS I4e) Téléphone: GOBelins 25-32 Compte ch. post.: 2048-66 - Georges Etienne Paris Specifier pour le comite international PRESIDENTS : Professeur Victor Basch. Professeur Paul Langevin. MEMBRES DIRECTEURS : Allemagne : Heinrich Mann. Rudolf Leonhard. Rudolf Breitscheid. Willy Munzenberg. Max Braun. Belgique : Louis de Brouckère. Canada : Prof. Mac Leod. Etats-unis : Dr. Ward. France : Léon Archimhaud. Emile Borel. Jacques Duclos. Léon Jouhaux. Jean Longuet. Jean Zyromski. Grande-bretagne : Sir Norman Angell. Ph. Noël Baker. Ben Tillett. Prof. P.M.S. Blackett. Viscount Churchill. Dorothy Woodmann. Hollande : Prof. Dr. B. Becker. Prof. A. G. Kranendonk. Dr. J. Schrijver. Dr. J. Tielrooy. Prof. Dr. Maarius Valkhoff Italie : Pietro Nenni. Luigi Campolonghi. Adami. Luxembourg : Lily Krier-Becker. Norvege Fredrik Haslund. Albert Raaen. Suéde : Rut Adler. Sénateur G. Branting. Suisse : Prof. R. Fischer. Prof. A. Oltramare. Hans Oprecht. Palestine : Antifa. Dr. Rafalkés. Tchécoslovaquie : A. Kunoszi. Em. V. Voska. Dr. J. Winternitz. Commission executive: Victor Basch. Président de la Ligue des Droits de l'Homme et du Rassemblement Populaire Français. — Paul Langevin, Professeur au Collège de France, Président du Comité Mondial contre la Guerre et le Fascisme. — Jean Chauvet, Secrétaire de la Commission de Solidarité du Rassemblement Populaire Français. — Buisson, Secrétaire de la C. G. T. — Isabelle Blume, Députée Socialiste Belge. — B. Cattanéo, Secrétaire du Comité Mondial des Femmes. — Bonnet, Délégué du Secours Rouge International. Secrétariat administratif : Madeleine Braun. Paris, le 12 June 1937 URGENT Dear Friends, Our Executive Commission, in session yesterday, voted to call a meeting of the Enlarged Executive Commission of the International Coordination Committee for the 26 and 27 of June, to which all movements, organisations, and individuals who have been working for Spain will be invited. At this conference, we will discuss the steps to be taken in all countries to make the anniversary of the first day of the civil war, July 18. 1937. a magnificent demonstration of solidarity with the Spanish Republic. Choose delegates for this conference at once, and prepare a plan of the propaganda which you intend to undertake in your country, in order that there may be some purposeful discussion of the concrete proposals presented by each national committee. You will receive, later, notice of the exact time and place of the conference, but we urge you now to keep the date in mind (June 26-27), and to make sure you are represented at this Executive Commission. trusting to hear from you shortly, we beg to remain, with fraternal greetings, For the Presidents of the International Committee: Professor Victor Basch Professor Paul Langevin MADELEINE BRAUN Secretary MB:bg 292/946/11/81